2004
DOI: 10.1210/jc.2003-031096
|View full text |Cite
|
Sign up to set email alerts
|

Increased C-Reactive Protein Levels in the Polycystic Ovary Syndrome: A Marker of Cardiovascular Disease

Abstract: The polycystic ovary syndrome (PCOS), one of the most common reproductive abnormalities, shares some components of the metabolic cardiovascular syndrome. Therefore, PCOS patients may represent the largest group of women at high risk for the development of early-onset cardiovascular disease (CVD) and/or diabetes. C-reactive protein (CRP) is a strong independent predictor of future CVD and/or stroke. Only one small published study has looked for such an association (17 PCOS patients vs. 15 controls). The objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
165
1
16

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(206 citation statements)
references
References 34 publications
24
165
1
16
Order By: Relevance
“…These include serum high sensitive C-reactive protein (hsCRP), homocysteine, sialic acid and fibrinogen [15][16][17][18]. Of these, the role of hsCRP in PCOS is gaining increasing interest [9].…”
Section: Introductionmentioning
confidence: 99%
“…These include serum high sensitive C-reactive protein (hsCRP), homocysteine, sialic acid and fibrinogen [15][16][17][18]. Of these, the role of hsCRP in PCOS is gaining increasing interest [9].…”
Section: Introductionmentioning
confidence: 99%
“…15 Boulman et al in their study found that 36.8% of the PCOS patients had hs-CRP levels above 5 mg/L, whereas only 9.6% of the controls exhibited such high hs-CRP levels (p<0.001). 2 In our study, metabolic syndrome was present in 36% of obese PCOS patients, but only 8% in the control group had metabolic syndrome. The mean hs-CRP level was 5.46 mg/L in PCOS patients and it is only 2.8 mg/L in non-PCOS control subjects (p<0.001).…”
mentioning
confidence: 40%
“…It has been found to correlate with traditional cardiovascular risk factors such as increasing age, obesity and adverse lipid profiles. 2 Clinically, PCOS can be diagnosed in women having hirsutism, irregular menstrual cycle and classical ovarian morphology. 3 Limited data are available concerning the prevalence of metabolic disorders in young women with PCOS and whether chronic PCOS status overtime will lead to greater impairment of cardiovascular status is still to be evaluated.…”
mentioning
confidence: 99%
“…CRP ile PKOS arasında yapılan univariant regresyonda anlamlı ilişki olsa da VKİ' nin katıldığı multivariant regresyonda CRP' deki bu anlamlı ilişki kaybolmuş, ancak VKİ ile devam eder görülmüştür. Bunu destekleyen diğer çalışmalarda da PKOS ve normal sağlıklı yetişkinlerde, hs-CRP ve leptin VKİ ile pozitif korelasyon gösterilmiştir [26][27][28][29]. Bu moleküller çoğunlukla artmış visseral adipoz doku ile ilişkilidirler [30,31,32].…”
Section: Bulgularunclassified
“…CRP'nin vasküler olaylarda iyi bir belirteç olması-nın yanında inflamatuar belirteç olarak da aterogenezde direkt rol oynadığı bildirilmiştir [7]. PKOS oluşumunda anahtar rol oynayan hiperinsülinemi ve yüksek CRP değerlerinin birlikteliği, kardiyovaskü-ler hastalıklarda önemli bir risk faktörüdür [8,9].…”
Section: Introductionunclassified